Teachers' Perceptions and Experiences of Menstrual Cycle Education and Support in UK Schools - Brown, Natalie; Williams, Rebekah; Bruinvels, Georgie; Piasecki, Jessica; Forrest, Laura J. (Frontiers in Global Women's Health, 2022)
The purpose of this study was two-fold, to 1) explore current education provision in UK schools including barriers to menstrual cycle education and 2) assess the perceived support teachers received to deliver menstrual cycle education. 789 teachers (91% female) from all stages of school education in England (48%), Scotland (24%), Wales (22%) and Northern Ireland (6%) completed an online survey. The survey captured information on menstrual education in schools, teacher’s knowledge and confidence of the menstrual cycle, support provided to teachers, provision of menstrual products in school and perceived impact of the menstrual cycle on young people in school. 498 teachers reported lessons were provided on the menstrual cycle (63%), predominantly delivered within personal, social, health and economic or science subjects, with over half of the lessons focusing on the biology (56%) or provision of menstrual products (40%) rather than lived experiences (14%). Teachers perceived the menstrual cycle affected participation in PE (88%), pupil confidence (88%), school attendance (82%) and attitude and behavior (82%). Overall, 80% of teachers felt receiving training would be beneficial to improve menstrual education. The results highlight education is scientifically focused, with less education on management of symptoms or lived experiences. Teachers also perceive the menstrual cycle to influence multiple aspects of school attendance and personal performance. There is a need to address menstrual education provided in schools across the UK to help empower girls to manage their menstrual cycle, preventing a negative impact on health and school performance.